2023
DOI: 10.1186/s13027-023-00500-3
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic antineoplastic activity of Toxoplasma gondii RH derived antigen against ehrlich solid carcinoma with evidence of shared antigens by comparative immunoblotting

Abstract: Background With cancer cases escalation, an urgent request to develop novel combating strategies arise. Pathogen-based cancer-immunotherapy is getting more consideration. Autoclaved parasitic antigens seem promising candidates, taking steadily their first steps. Our aim was to examine the prophylactic antineoplastic activity of autoclaved Toxoplasma vaccine (ATV) and to test for the shared antigen theory between Toxoplasma gondii and cancer cells. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Eissa et al. demonstrated that mice immunized with autoclaved Toxoplasma vaccine (ATV) produced 13.3% inhibition of Ehrlich solid carcinoma (ESC) genesis and confirmed the existence of at least four pairs of common antigens between ATV and ESC ( Eissa et al., 2023 ). Subsequent results showed that ATV and cyclophosphamide synergistically exerted a stronger tumor immune response and anti-angiogenesis effect in ESC-bearing mice, indicating that ATV has the potential to be a tumor vaccine or cancer drug adjuvant ( Ismail et al., 2023 ).…”
Section: T Gondiimentioning
confidence: 99%
“…Eissa et al. demonstrated that mice immunized with autoclaved Toxoplasma vaccine (ATV) produced 13.3% inhibition of Ehrlich solid carcinoma (ESC) genesis and confirmed the existence of at least four pairs of common antigens between ATV and ESC ( Eissa et al., 2023 ). Subsequent results showed that ATV and cyclophosphamide synergistically exerted a stronger tumor immune response and anti-angiogenesis effect in ESC-bearing mice, indicating that ATV has the potential to be a tumor vaccine or cancer drug adjuvant ( Ismail et al., 2023 ).…”
Section: T Gondiimentioning
confidence: 99%